2018
DOI: 10.1186/s13046-018-0987-9
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone induces apoptosis through ROS-mediated ER stress and inhibition of STAT3 in prostate cancer cells

Abstract: BackgroundProstate cancer is one of the most commonly diagnosed cancers in men worldwide. Currently available therapies for metastatic prostate cancer are only marginally effective. Therefore, new therapeutic agents are urgently needed to improve patient outcome. Isoalantolactone (IATL), an active sesquiterpene naturally present in many vegetables and medicinal plants, is known to induce cell death and apoptosis in various cancer cell lines. Nevertheless, antitumor mechanisms initiated by IATL in cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 33 publications
(36 reference statements)
2
47
0
Order By: Relevance
“…Severe ER stress has the ability to initiate another atypical intrinsic apoptosis response [ 200 ]. Induction of ER stress activation and PCa cell apoptosis by both Chelerythrine (CHE) and Isoalantolactone (IALT) is dependent on ROS generation [ 193 , 201 ]. Mechanically, IALT increases the levels of ROS-dependent p-eIF2 α and ATF4 in the PC-3 and DU145 cells, thus stimulating expression of the transcription factor CHOP that inhibits the expression of Bcl-2 and is strictly responsible for the initiation of the cell apoptosis cascade [ 201 203 ].…”
Section: Roles Of Ros Molecules In Pcamentioning
confidence: 99%
See 1 more Smart Citation
“…Severe ER stress has the ability to initiate another atypical intrinsic apoptosis response [ 200 ]. Induction of ER stress activation and PCa cell apoptosis by both Chelerythrine (CHE) and Isoalantolactone (IALT) is dependent on ROS generation [ 193 , 201 ]. Mechanically, IALT increases the levels of ROS-dependent p-eIF2 α and ATF4 in the PC-3 and DU145 cells, thus stimulating expression of the transcription factor CHOP that inhibits the expression of Bcl-2 and is strictly responsible for the initiation of the cell apoptosis cascade [ 201 203 ].…”
Section: Roles Of Ros Molecules In Pcamentioning
confidence: 99%
“…Induction of ER stress activation and PCa cell apoptosis by both Chelerythrine (CHE) and Isoalantolactone (IALT) is dependent on ROS generation [ 193 , 201 ]. Mechanically, IALT increases the levels of ROS-dependent p-eIF2 α and ATF4 in the PC-3 and DU145 cells, thus stimulating expression of the transcription factor CHOP that inhibits the expression of Bcl-2 and is strictly responsible for the initiation of the cell apoptosis cascade [ 201 203 ]. Mitochondrial outer membrane permeabilization (MOMP) also results in elevated cytoplasmic proapoptotic molecules containing apoptosis-inducing factor (AIF) and endonuclease G (Endo G) in response to organelle damage induced by ROS, and these molecules function in a caspase-independent manner [ 204 ].…”
Section: Roles Of Ros Molecules In Pcamentioning
confidence: 99%
“…Promote its transcription [30]. The results showed that the STAT3 phosphorylation was decreased, indicating that PN can block the phosphorylation of STAT3, thereby preventing its entry into the nucleus.…”
Section: Discussionmentioning
confidence: 93%
“…Celastrol, which contains a reactive quinone methide moiety enabling covalent attachment to cysteine residues (49), including direct binding and inhibition of c-Myc-Max heterodimers (50), cancerous inhibitor of protein phosphatase 2A (CIP2A) (51), STAT3 (52), SHOC-2 to inhibit ERK signaling (53), IKKα and IKKβ (54), and HSP90-chaperone interactions (55-57); directly binds nearly 70 protein targets in a proteome microarray assay (53); and affects other cellular signaling pathways including protein phosphatase 2A-Akt, AMPK, and WNT/β-catenin (58). Isoalantolactone activates AMPKα (28) and inhibits STAT3 (59) and IKKβ (60). Camptothecin inhibits topoisomerase I (61).…”
Section: Discussionmentioning
confidence: 99%